Hydrological, socioeconomic and ecological impacts of the North Atlantic oscillation in the Mediterranean Region - Vicente Serrano, S. M. (Sergio M.).; Trigo, Ricardo Machado; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
The Mediterranean basin represents one of the most important ?hot spots? of climate change in the world, with recent trends towards a hotter and drier climate being related to changes in atmospheric circulation patterns. Such changes can have significant impacts in the climate of this region but also on the natural environment and several socioeconomic activities. Among these patterns, the North Atlantic Oscillation (NAO) is one of the main forcing factors in the region with impact on extreme events such as droughts, severe precipitations or heat and cold waves, the availability of water resources, the ecological dynamics, the quality and quantity of crops, the migration and welfare of animal populations, the fisheries dynamics, the triggering of landslides and the air pollution and human health, among others.  The aim of Hydrological, Socioeconomic and Ecological Impacts of the North Atlantic Oscillation in the Mediterranean Region, is to serve as an updated reference text  that covers the wide range of evidences on the NAO impacts in the Mediterranean regions and from a multidisciplinary perspective.  This volume constitutes a unique document to present the state of the art of the numerous studies undertaken on the hydrological, socioeconomic and ecological impact of the NAO, collecting the expertise of researchers from several complementary earth science fields (geography, hydrology, remote-sensing, climatology, agriculture, energy), but that have been lacking a common ground.
Editorial: Hydrological, socioeconomic and ecological impacts of the North Atlantic Oscillation in the Mediterranean region -- Variability and changes in the North Atlantic Oscillation index -- The NAO impact on droughts in the Mediterranean region -- The impacts of the NAO on hydrological resources of the western Mediterranean -- The impacts of NAO on the hydrology of the eastern Mediterranean -- Influence of winter North Atlantic Oscillation index (NAO) on climate and snow accumulation in the Mediterranean mountains -- Impact of NAO on Mediterranean fisheries -- Impacts of the NAO on Mediterranean crop production -- The impacts of the NAO on the vegetation activity in Iberia -- Direct and indirect effects of the North Atlantic Oscillation on tree growth and forest decline in northeastern Spain -- Ecological impacts of the North Atlantic Oscillation in Mediterranean ecosystems -- Impacts of the NAO on atmospheric pollution in the Mediterranean basin -- Evaluation of the relationship between the NAO and rainfall erosivity in northeastern Spain during the period 1955-2006 -- Impacts of the North Atlantic Oscillation on landslides -- The impact of the NAO on the solar and wind energy resources in the Mediterranean area.
Electronic reproduction.
Keywords: North Atlantic oscillation; Geology; Science; Electronic books